Worked examples for the design of concrete structures to Eurocode 2 - Threlfall, A. J. (Boca Raton : CRC Press, 2013)
'Packed with worked examples, this practical design guide illustrates how Eurocode 2 may be used in practice. A short introduction outlines the fundamental objectives of design and referring to relevant sources of information for loads and material properties. The book then presents complete and detailed designs of six archetypal structures, civil structures as well as buildings. This comprehensive treatment of the variety of structures to the new code make this a unique and invaluable work. Covers a range of structures, not just buildings. Deals fully with the analysis of the structure and the design and detailing of the members. Conforms to the latest standards and recommendations'--
Includes bibliographical references and index.
Keywords: Concrete construction -- Europe -- Problems, exercises, etc; EN1992 Eurocode 2 (Standard) -- Problems, exercises, etc; TECHNOLOGY & ENGINEERING / Civil / General